Survey Of Healthy Living Patterns Of Students Of Health FKIP Undana Students In The Covid-19 Pandemic - Al Ihzan Tajuddin; Yudabbirul Arif; Erwin S Neolaka; Ronald Dwi Ardian Fufu; Michael Johannes Hadiwijaya Louk (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
At this time the phenomenon that is happening right now is in a new lifestyle, which as we understand it about healthy living, keeping a distance and so on can be called the new normal, because the main reason is the corona virus. The problem is based on what it can be seen that the lifestyle of many students is not healthy for that a survey related to the lifestyle of students is carried out. This research is a descriptive research using survey method. The population in this study were Physical Education and Health Students at Nusa Cendana University. The sample in this study used simple random sampling, the research sample was 80 students from the Physical Education and Health Center of Nusa Cendana University. By giving a questionnaire to students who are the subjects in the research. This research instrument uses a questionnaire in the form of a written statement given through a google form to the respondent. Based on the results of data analysis and discussion, it can be concluded that the healthy lifestyle of FKIP Undana Penjaskesrek students during the COVID-19 pandemic was in the "never" category by 15% (6 students), "rarely" by 35% (14 students), " often” by 38% (15 students), “often” by 13% (5 students). Based on the average score, which is 139.58, the healthy lifestyle of FKIP Undana Penjaskesrek students is in the "Frequent" category. In the sense that the FKIP Undana Penjaskesrek students during the covid 19 period often apply a healthy lifestyle.